Effects of Green Roof on the Wind Field of a Low-rise Building. (2015) - Wai, Wing-Hong Onyx; Hu, Wen-Qing; Li, Chi-Wai; Zhan, Jie-Min
Abstract: A three dimensional numerical wind tunnel based on the Navier-Stokes equations for viscous, incompressible fluid and LES method is established. Incoming wind field is generated based on the AIJ guidelines (2004). The numerical wind tunnel is validated against experimental results. A low-rise building with green roof is tested in the numerical wind tunnel. The results show that the green roof reduces the drag force of the building, cuts down the fluctuation near the roof, but has insignificant effect on the time-averaged velocity field.